Optical Solitons and Rogue wave solutions of NLSE with variables coefficients and modulation instability analysis - Aslan, Ebru Cavlak; İnç, Mustafa (Univ Tabriz, 2022)
In this work, we investigate soliton solutions of the generalized variable coefficients nonlinear Schrodinger equation. The Jacobi elliptic ansatz method is applied to obtain the optical soliton solutions. The necessary conditions that warrant the presence of these solutions are determined. We consider the Lie symmetry analysis of governing equation. Also, the stability of this equation is analyzed by the modulation instability.
Keywords: NLSE; Modified Jacobi elliptic functions; Optical soliton; Rogue wave; The exp-function approach